Nonstationary flows and shock waves - Glass, Irvine I. (Clarendon Press,Oxford University Press, 1994)
An understanding of nonstationary gas flows (and liquids under high pressure) is of critical importance to engineers studying phenomena such as shock waves arising from an explosion of energy in a limited space, the behavior of media through which the shock propagate, and the nonstationary motion of a mixture of gases in energy-producing devices and engines. In this authoritative and well-written book, the reader will find comprehensive treatments of all important aspects of shock-tube and shock-wave research in pure and dusty gases, as well as of dissociated and ionized boundary layers, spherical and cylindrical explosion and implosion phenomena, hypervelocity launchers, and shock-wave reflections, diffractions, and refractions. Unique in its deft combination of analytical, numerical, and experimental work, the book expertly covers 40 years of continuous research in the area. It will be sought after by mechanical engineering students and researchers interested in explosion and blast wave phenomena